Healing verses (As-Syifa verses): A proposed novel therapy approach to reduce stress in drug addiction - Samhani, Ismail; Mohd Shahril, Othman; Rohayah, Husain; Nasir, Mohamad; Syed Hadzrullathfi, Syed Omar; Khairi, Che Mat; Zulfa Izza, Mohamed@Hashim (2017)
Stress increases internalized and psychosocial vulnerability in development of illicit drug abuse. Studies showed stress initiates and escalates drug abusive behavior as coping strategies to deal with stressors and to self-medicate. Their brain also exhibited altered patterns of connectivity which reduced of self-control over impulses thus making self-reward a compulsory need